2009
DOI: 10.1002/rra.1175
|View full text |Cite
|
Sign up to set email alerts
|

Habitat used by Macrhybopsis chubs associated with channel modifying structures in a large regulated river: implications for river modification

Abstract: We examined use of channel modifying structures (CMS; e.g., engineered rock dikes, channel sandbars) and their associated smaller spatial-scale habitats (SSH) on lower Missouri River, USA, by speckled chub (Macrhybopsis aestivalis), sicklefin chub (M. meeki) and sturgeon chub (M. gelida) from June through October, 2006 to identify important habitat characteristics that could aid conservation. We sampled chubs primarily in six CMS types: L-dikes, wing-dikes, kicker dikes, rootless dikes, channel sandbars and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 49 publications
0
36
0
2
Order By: Relevance
“…(); 10 Ridenour et al. (); 11 Miranda and Killgore (); 12 Luttrell et al. (); 13 Hesse (); 14 Hampton and Berry Jr (1997); 15 Herzog, Ostendorf, Hrabik and Barko (); 16 Hatch et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(); 10 Ridenour et al. (); 11 Miranda and Killgore (); 12 Luttrell et al. (); 13 Hesse (); 14 Hampton and Berry Jr (1997); 15 Herzog, Ostendorf, Hrabik and Barko (); 16 Hatch et al.…”
Section: Resultsmentioning
confidence: 99%
“…Western silvery minnow, plains minnow and Red River shiner were reported from backwaters, side channels, mainstream borders and depressional environments (Hesse, ; Houston, ; Kilgore & Rising, ; Welker & Scarnecchia, ). Conversely, sturgeon chub and Pecos bluntnose shiner were reported in swift velocity mainstem habitats (Kehmeier, Valdez, Medley & Myers, ; Ridenour, Starostka, Doyle & Hill, ; Welker & Scarnecchia, ). Despite the commonalities in mesohabitat, habitat partitioning between western silvery minnow and plains minnow has been observed at finer spatial scales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has confirmed M . meeki are litho‐pelagophils, where the eggs and larvae have a drifting phase and previous studies have found that juveniles are found in inshore shallow habitats (Reeves, ; Ridenour et al ., ; Starks et al ., ). As with other riverine broadcast spawners, retention of M .…”
Section: Discussionmentioning
confidence: 99%
“…For example, different mesohabitat types (e.g., large islands) are formed above and below the confluence zone in the mainstem, which maintain different fish communities from the naturally flowing reaches to some extent (Ridenour et al 2009(Ridenour et al , 2011. Since the number, distribution and significance of different mesohabitat patches differ among the different basin types (e.g., heart vs elongated), differences in their effect on the assembly of fish communities among the different basin types are expected.…”
Section: Patterns In Diversitymentioning
confidence: 99%